2020
DOI: 10.1108/ijhg-03-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Scoping the application of primary care advanced clinical practice roles in England

Abstract: PurposeThis study aims to scope the profile and application of an advanced clinical practitioner (ACP) roles in primary care in the North of England and how these roles meet the requirements of Health Education England's (HEE’s) ACP workforce capability framework.Design/methodology/approachA two-stage design was used. Stage 1 analysed health and social care workforce intelligence reports to inform scoping of numbers of ACPs working in primary care. Stage 2 used two surveys. Survey 1 targeted ACP leads and coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Inman (2019) found that clinical skills are acquired early in postgraduate programme, perhaps underpinning the inconsistent approach to educational standards. This echoes with the work of Thompson et al (2020) as their survey of clinical leads also identified differences in the academic requirements of posts with some requiring an MSc or just clinical skills and prescribing modules. Prescribing remains a challenge regarding the omniprofessional role with variations in scope between professions, and although some roles did acknowledge that independent prescribing may not be within the gift of some applicants, most did require individuals to have this status.…”
Section: Discussionmentioning
confidence: 83%
“…Inman (2019) found that clinical skills are acquired early in postgraduate programme, perhaps underpinning the inconsistent approach to educational standards. This echoes with the work of Thompson et al (2020) as their survey of clinical leads also identified differences in the academic requirements of posts with some requiring an MSc or just clinical skills and prescribing modules. Prescribing remains a challenge regarding the omniprofessional role with variations in scope between professions, and although some roles did acknowledge that independent prescribing may not be within the gift of some applicants, most did require individuals to have this status.…”
Section: Discussionmentioning
confidence: 83%
“…The absence of distinct boundaries was identified as a barrier by ACPs in Thompson et al (2020) This unique study showed that there is potential for interprofessional tensions among the new non-medical practitioners themselves. The use of hierarchal terms to describe each group was common, such as the clinical skills of physician associates are positioned between those of a nurse and doctor.…”
Section: Theme 3: Lack Of Familiarity With the Role As A Barriermentioning
confidence: 88%
“…All 11 papers identified that existing members of staff in general practice reported a limited awareness of the role of an ACP, FCP, PA, PP and CP. Thompson et al (2020); Evans et al (2020); Hook and Walker (2020), revealed a consistent concern with the paucity of knowledge regarding the educational requirements needed to become an ACP. Indeed, similar concerns were raised regarding the qualifications of pharmacists (Ryan et al 2018) and paramedics (Schofield et al 2020).…”
Section: Theme 3: Lack Of Familiarity With the Role As A Barriermentioning
confidence: 96%
“…The inconsistency of the job titles in this level of practice is associated with lack of role recognition that affects acceptance in the clinical setting and may even lock practitioners into their workplaces, hindering movement between healthcare organizations. 11,42,43 Regarding AP's group, only about one-third had a job plan for their working time with specific times allocation by AP pillar. (This question was not addressed in the other subsection).…”
Section: Governance and Sustainabilitymentioning
confidence: 99%